Custos de conformidade à tributação: um estudo de caso em uma empresa estadual de saneamento - Maia, Glavany Lima (2007)
The compliance costs of taxation correspond to the costs incurred by taxpayers in meeting the legal tax requirements. They include the costs of time and resources consumed in activities, such as the calculation and retention of taxes and contributions, filling the returns, dealing with the tax authority audit, and expenses on tax planning, research and training, among others. The subject has attracted international interest, with the relatively recent development of researches around the world, but there are still few studies about this topic in Brazil. This work aims, by means of bibliographical and documental research and case study, to assess the perception of managers and collaborators of a state company of sanitation with respect to the compliance costs of taxation. The results obtained with structured questionnaires and semistructured interviews show that since there is no investigation or control of the compliance costs of taxation in the evaluated company, there is an intuitive perception of not only the existence of these costs but also their growth, mainly due to the complexity and instability of fiscal rules. Although the interviewed people agree on the importance of the subject, it is still not a tax matter usually discussed within the evaluated company, which prioritizes the fiscal planning aiming the taxes reduction.